AnnexinA6: a potential therapeutic target gene for extracellular matrix mineralization - Yang, Jie; Pei, Tong; Su, Guanyue; Duan, Peiyan; Liu, Xiaoheng (Frontiers in Cell and Developmental Biology, 2023)
The mineralization of the extracellular matrix (ECM) is an essential and crucial process for physiological bone formation and pathological calcification. The abnormal function of ECM mineralization contributes to the worldwide risk of developing mineralization-related diseases; for instance, vascular calcification is attributed to the hyperfunction of ECM mineralization, while osteoporosis is due to hypofunction. AnnexinA6 (AnxA6), a Ca 2+ -dependent phospholipid-binding protein, has been extensively reported as an essential target in mineralization-related diseases such as osteoporosis, osteoarthritis, atherosclerosis, osteosarcoma, and calcific aortic valve disease. To date, AnxA6, as the largest member of the Annexin family, has attracted much attention due to its significant contribution to matrix vesicles (MVs) production and release, MVs-ECM interaction, cytoplasmic Ca 2+ influx, and maturation of hydroxyapatite, making it an essential target in ECM mineralization. In this review, we outlined the recent advancements in the role of AnxA6 in mineralization-related diseases and the potential mechanisms of AnxA6 under normal and mineralization-related pathological conditions. AnxA6 could promote ECM mineralization for bone regeneration in the manner described previously. Therefore, AnxA6 may be a potential osteogenic target for ECM mineralization.